UNCERTAINTY EVALUATION OF SMART CARDIO DEVICE - Insani, Asep; Khusni, Uus; Sugiarto, Anto Tri (Instrumentasi, 2021)
Electrocardiograph (ECG) is a device used to measure electrical activity from the heart. The existence of abnormalities in the heart, it requires a tool to detect the symptoms of the disorder earlier so that a Smart Cardio Device is made with an intelligent system. This intelligent system is used to detect ECG output signals and separate them from normal ones with those with disease disorders. In determining the validity of the ECG signal that is released by the tool made, a standard system is needed to justify the signal. Of course, it takes experts who are competent in their field to determine this. This research collaborates with one of the calibration labs made by the National Standardization Agency (BSN) with calibration researchers who are experts in the ECG field who are developing a method specifically for calibrating ECG signals. The general calibration method used is the internal calibration method with calibration features on ECG devices and external calibration with the help of patient simulator. In this study external calibration methods were used, namely methods that take into account the validity or validity of measurements by looking at the value of uncertainty. The thing that is done in determining this uncertainty is the calculation of values by making several measurements to get the value of the degree of effective freedom and an expanded uncertainty value. The result shows the value of the effective degree of freedom is 93, 91 mV and the uncertainty value that is extended is 0.058 mV.